2016
DOI: 10.1590/1414-431x20165326
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviates pulmonary angiogenesis in a rat model of hepatopulmonary syndrome

Abstract: Quercetin shows protective effects against hepatopulmonary syndrome (HPS), as demonstrated in a rat model. However, whether these effects involve pulmonary vascular angiogenesis in HPS remains unclear. Therefore, this study aimed to assess the effect of quercetin on pulmonary vascular angiogenesis and explore the underlying mechanisms. Male Sprague-Dawley rats weighing 200-250 g underwent sham operation or common bile duct ligation (CBDL). Two weeks after surgery, HIF-1α and NFκB levels were assessed in rat lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The authors correlated the observed benefits with a potential role of Quercetin as a ROS and oxidant scavenger, along with its known ability to reduce inflammatory cytokine production (in particular TNFα) via modulation of NF-κβ1 and Iκβ pathways (Nair, et al, 2006). Moreover, supplementation of Quercetin in a rat model of hepatopulmonary syndrome showed anti-angiogenic effects associated with AKT/NF-κB and VEGFA/VEGFR-2 pathways (X. Li, et al, 2016).…”
Section: Pharmacological Approaches Targeting Tlr/nf-κb and Oxidatmentioning
confidence: 99%
“…The authors correlated the observed benefits with a potential role of Quercetin as a ROS and oxidant scavenger, along with its known ability to reduce inflammatory cytokine production (in particular TNFα) via modulation of NF-κβ1 and Iκβ pathways (Nair, et al, 2006). Moreover, supplementation of Quercetin in a rat model of hepatopulmonary syndrome showed anti-angiogenic effects associated with AKT/NF-κB and VEGFA/VEGFR-2 pathways (X. Li, et al, 2016).…”
Section: Pharmacological Approaches Targeting Tlr/nf-κb and Oxidatmentioning
confidence: 99%
“…Salvia Miltiorrhiza and puerarin improved the thrombus status by regulating the level of VEGF and the release of coagulation factors ( Hu et al, 2020 ). In a rat model of hepatopulmonary syndrome, quercetin predominantly inhibited pulmonary vascular angiogenesis by regulate VEGFA/VEGFR-2 pathways ( Li et al, 2016 ). Moreover, acacetin played an anti-inflammatory role by regulating the VEGFA ( Li and Ren, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In the literature, there are articles reporting that the angiogenesis is decreased in the tumor groups as a result of factor VIII staining in studies with plants with antioxidant properties (Cornus mas L, curcumin, resveratrol, Viburnum opulus, quercetin). 8 11,35 37 Yang et al showed that AuNPs-Qu-5 inhibits angiogenesis and metastasis of quercetin in breast cancer cells tested by targeting the EGFR/ vascular endothelial growth factor receptor 2 (VEGFR-2) signal pathway. 5 In our study, the expression of FVIII in solid tumor masses was evaluated and the decrease in FVIII expression was found statistically significant in the groups given quercetin ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%